Apocalypticism and eschatology in late antiquity encounters in the Abrahamic religions, 6th-8th centuries : Beyond the fathers, volume 2 - Amirav, Hagit; Grypeou, Emmanouela; Sṭrumzah, Gedalyahu Gʹ. 1948- (Leuven Paris Bristol, CT Peeters, 2017)
This volume includes papers on ancient apocalypticism and eschatology in the crucial period prior to the advent of Islam in the Mediterranean basin, and through the period (the sixth to the eighth centuries) when this new religion took roots and established itself in the area. As these were important social, religious, and cultural phenomena, the contributors to this volume - specialists in Late Antique and Byzantine, Syriac, Jewish, and Arabic studies - have investigated them from a variety of angles and foci, rendering this volume unique in terms of its interdisciplinary approach and broad scope. In this regard, 'Apocalypticism and Eschatology in Late Antiquity' should be read as complimentary to the previous volume in the series, 'New Themes, New Styles in the Eastern Mediterranean', where similar goals were set and met, namely to understand not only how the Christian and Jewish populations responded to the dramatic political and military changes, but also how they expressed themselves in existing, reinvented, and new literary means at their disposal
Keywords: Abrahamic Religions; Apocalyptic Literature; Civilization, Ancient; Eschatology; History, Ancient; Religion; Konferenzschrift -- 2013 -- Oxford